Diarrhea is a positive outcome predictor for sorafenib treatment of advanced hepatocellular carcinoma - Koschny, Ronald; Gotthardt, Daniel; Jäger, Dirk; Stremmel, Wolfgang; Ganten, Tom M. (Oncology, 2013)
Objective: This study was performed to identify clinical predictors for better survival in patients with advanced hepatocellular carcinoma (HCC) under sorafenib treatment. Methods: Between December 2007 and January 2010, 46 patients with advanced HCC were treated with sorafenib until significant tumor progression or intolerable toxicity. We prospectively collected clinical baseline data as well as data on the incidence and severity of toxic side effects of sorafenib to be correlated with progression-free survival and overall survival (OS), respectively. Results: Only 26.1% (n = 12) of patients tolerated sorafenib without requiring dose reduction. The most frequent grade 3 toxicities were diarrhea (32.6%), hand-foot skin reaction (13.0%), fatigue (4.3%), and nausea/vomiting (2.2%). Eastern Cooperative Oncology Group performance status (p = 0.034) and portal vein infiltration (p = 0.021) significantly correlated with OS. Furthermore, we found a significant correlation between OS and appearance of grade 2 or 3 diarrhea with a median actuarial survival of 11.8 months (95% CI 6.9-16.6) compared to 4.2 months in patients with grade 0 or 1 diarrhea (95% CI 0.0-9.1; p = 0.009). In contrast, appearance of hand-foot skin reaction did neither correlate with progression-free survival nor with OS. Conclusion: Appearance of grade 2 or 3 diarrhea indicates a better OS of HCC patients undergoing sorafenib treatment.